Examination of Changes in Enzyme Activities of Erythrocyte Glucose 6-Phosphate Dehydrogenase and 6-Phosphogluconate Dehydrogenase in Rats Given Naringenin and Lead Acetate - Demirdag, Ramazan; Comakli, Veysel; Ozkaya, Ahmet; Sahin, Zafer; Dag, Uzeyir; Yerlikaya, Emrah; Kuzu, Muslum (Wiley, 2015)
In our study, controlled experimental groups were performed by giving substances Lead acetate, Naringenin and Naringenin + Lead acetate to rats in vivo conditions Changes in the glucose 6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate dehydrogenase (6PGD) enzyme activities in erythrocytes of rats in these groups were compared to the Control group. An inhibition significant degree for G6PD enzyme activity was observed in all groups when compared to the Control group (p < 0.001). While inhibition significant degree for 6PGD enzyme activity was observed in Lead acetate groups (p < 0.001), no significant effect was observed in the Naringenin and Naringenin + Lead acetate groups (p > 0.05). In addition, lead levels in the groups of rats were determined using an inductively coupled plasma mass spectrometer (ICP-MS) device. As a result of measurements by the ICP-MS device, lead levels were found as an average of 42.9 +/- 2.51, 36.71 +/- 1.13, 172.16 +/- 9.63, and 95.07 +/- 5.87 ppm in the Control, Naringenin, Lead acetate and Naringenin + Lead acetate groups, respectively. Our results were shown that Naringenin has protective effects on the Lead acetate induced oxidative stress erythrocytes in rat.
Keywords: Metal; Naringenin; Glucose 6-Phosphate Dehydrogenase; 6-Phosphogluconate Dehydrogenase; Inhibition